Geographical analysis of the poultry in Wasit governorate (Journal of the College of Education for Women, 2019)
This study aims to discuss the projects of poultry in Wasit province in 2013 and geographical distribution according to the type and contrast on the level of administrative units representing Districts and The reasons for this discrepancy, as well as knowledge of the factors affecting the distribution by the analysis and reasoning and description This study divided to the four themes, The first of the statement of nutritional importance and economic Poultry focused on the importance of various poultry products, The second one shows the relative position of the province of Wasit between the provinces of Iraq in poultry and production of eggs and meat farming projects, and then followed by the third one (theme) as it ensures the geographical distribution of projects in poultry in the districts of the province of Wasit and production of eggs and meat on the six districts level Finally, the fourth one (theme) indicating the geographic factors affecting the poultry in the province enhanced the number of maps, tables and charts and concluded with in conclusions which the researcher achieved. The researcher raises some recommendations, which she sees a field for advancement of poultry breeding and development in the province of Wasit.The study concluded that the Wasit province ranked sixth place in the poultry projects and meat production by 122 Project, by 5.2% and 7422 tons, by (7.3%) of the total projects and meat production in the provinces of Iraq in 2013, while the province of Wasit fifth rank producingeggs by 19,800 egg, by (2.3%) of the total egg production in Iraq in the same year, also contributed to a number of geographical creating a favorable environment for poultry factors in Wasit province, particularly the availability of materials used in the feed and provide manpower and proximity to centers consumption, which encouraged the practice and development of poultry project .